The Inhibitory Effect and Mechanism of Action of Myricaria germanica Essential Oils on Skin Inflammation based on Network Pharmacology and Molecular Docking - Liu, Likuan; Wang, Mingjin; Zhang, Junyan; Chen, Wenqing; Zuo, Wenming; Zeng, Yang; Li, Jinping (Letters in Drug Design & Discovery, 2024)
BackgroundCurrently, network pharmacology and molecular docking technology are valuable tools frequently employed to predict the mechanisms and targets of drugs. Wengbu, a Tibetan medicine, is an anti-inflammatory agent commonly used in the Qinghai-Tibet Plateau of China, and it has been demonstrated to have an effect against skin inflammation. However, the network pharmacological mechanisms and targets of Wengbu in relation to skin inflammation have not yet been reported. This paper aims to provide a scientific basis for the anti-skin inflammatory effects of Wengbu through experimental verification based on the predicted targets.MethodsThe chemical constituents and targets of Myricaria germanica essential oil were identified through a literature search, as well as databases such as PubChem and Swiss Target Prediction. Targets associated with skin inflammation were obtained from the Gene Cards human gene database, DisGeNET, and the OMIN databases. Subsequently, a Myricaria germanica essential oil-skin inflammation target database and a corresponding target network diagram were constructed. Biological function enrichment analysis and molecular docking verification were then conducted. In vitro cell experiments were performed to validate the role of Myricaria germanica essential oil's key targets in inhibiting skin inflammation.ResultsTen compounds were selected through a literature review, including linalool, eugenol, and vanillin. A total of 429 essential oil component targets, 889 skin inflammation targets, and 108 intersection targets were identified. MAPK1, PIK3CD, PIK3CA, and MAPK14 could be the principal targets of Myricaria germanica. essential oil to reduce skin inflammation. The principal signaling pathways through which Myricaria germanica essential oil exerts its anti-inflammatory effects include the cancer pathway, coronavirus disease (COVID-19), lipid metabolism, and atherosclerosis. These effects may be attributed to the regulation of the cellular inflammatory response, the cellular response to lipopolysaccharide, and the positive regulation of cytoplasmic calcium concentration. Molecular docking results indicated that the potential components of Myricaria germanica essential oil exhibited strong binding affinity with the core target proteins. In vitro cell experiments demonstrated that Myricaria germanica essential oil effectively reduced the levels of TNF-α, IL-6, and Caspase-3, decreased the levels of reactive oxygen species (ROS) and malondialdehyde (MDA) in cells, and enhanced the activity of superoxide dismutase (SOD), thereby inhibiting skin inflammation.ConclusionMyricaria germanica essential oil exhibits multi-component, multi-target, and multi-pathway characteristics in the inhibition of skin inflammation. This experiment serves as a reference and foundation for further elucidating its material basis and the mechanisms involved in inhibiting skin inflammation.
Keywords: Myricaria germanica essential oil